Which exerts a greater impact on ecosystem resilience: Cropland expansion or urban expansion? Insights from a spatiotemporal analysis - Jinhua Wu; Hongwei Wang; Can Wang; Xin Huang; Zhenggang Wang; Chi Zhang; Bei Chen; Yilinuer Yiming; Chunshan Zhou (Ecological Informatics)
Ecosystem resilience (ER) is pivotal for regional ecological security and sustainable ecosystem development. Both cropland expansion and urban expansion impact ER; however, the comparative magnitude and spatial patterns of their effects remain underexplored. This study investigates the spatiotemporal evolution and distribution characteristics of ER in the Northern Slope Economic Belt of the Tianshan Mountains (NSEBTM) from 2000 to 2020, using Fragstats and ArcGIS. A combination of the Geo-informatic Tupu method, Zonal Statistics, and Standard Deviation Ellipse analysis was employed to assess and compare the positive (ecological adaptive expansion, EAE) and negative (ecological trade-off expansion, ETE) impacts of cropland and urban expansion on ER. ER levels in the NSEBTM remained low throughout the study period, with a turning point occurring in 2010, followed by gradual improvement. Spatially, ER exhibited a “northwest high, southeast low” distribution pattern, with high-value regions clustering in the northwest and low-value regions dispersing in the southeast. Both cropland and urban expansion exerted dual impacts on ER, with ETE effects dominating in the central and western areas and EAE effects prevailing in the eastern areas. Notably, cropland expansion had broader and more intense negative impacts on ER than urban expansion, with cropland changes affecting larger areas and exhibiting more pronounced ecological trade-offs. These findings highlight the need for sustainable land-use strategies that reconcile ecological preservation with the demands of agricultural and urban development.